Contesting the Toilet: Colonial Discourses, Elite Protests, and Religious Sentiments on Public Sanitation Infrastructure in Bombay City - Satam, Mrunmayee (International Planning History Society Proceedings, 2024)
Public toilets have always been an intensely politicised site. Focusing on the colonial discourses of a ‘contaminated city’ and its implications for public health, this paper explores the politics surrounding the construction of public toilets in colonial Bombay City. The paper relies extensively on the Standing Committee and Corporation Committee debates to examine the complex dynamics of the public space, infrastructure, governance, and urban politics. Firstly, the paper traces the development of sanitation policy in the city and highlights how offensive odours, inadequate sanitary infrastructure and urban contamination were identified as the key factors in the spread of diseases at the turn of the twentieth century. Secondly, this paper delves into the protests of city elites against the construction of public toilets in their neighbourhoods, exploring how their concerns over the economic value of their land and the perception of public toilets as 'insanitary' spaces led them to utilize their social standing to influence urban planning and hinder the implementation of essential sanitation infrastructure. Finally, the paper investigates the contentious interplay between religious sentiments and the construction of public toilets in their vicinity, revealing how conflicts arising from the perception of sacrilege and religious sensitivities hindered effective sanitation infrastructure development and public health initiatives.